Nilai (Paca) Belis dalam Budaya Perkawinan Masyarakat Manggarai di Kelurahan Golo Wangkung Kecamatan Congkar Kabupaten Manggarai Timur - Flaviana Herlis; Gregorius Neonbasu; Yohana Fransiska Medho (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to uncover, analyze, and document the cultural values embodied in the paca or belis tradition in Manggarai community weddings in Golo Wangkung Village, Congkar District, East Manggarai Regency. The belis tradition is understood as an important element in wedding customs that symbolizes the groom's family's respect for the bride's family for their services in raising and educating their daughter until she is ready to start a household. This study uses a qualitative approach with descriptive methods, utilizing data collection techniques through participatory observation, in-depth interviews with traditional leaders, the bridal couple, and local residents, as well as documentation of the traditional procession. The results show that belis not only contains economic value through the provision of material or livestock, but is also full of social, cultural, and spiritual meaning. The main values identified include respect for parents and ancestors, the responsibility of the groom's family for the continuity of family relationships, strengthening social ties between two extended families, and a symbol of the legitimacy of marriage according to Manggarai customs. The belis tradition also functions as a mechanism to maintain harmonious relationships between families and strengthen social networks within the community. Furthermore, this tradition plays a strategic role in maintaining local cultural identity amidst modernization and changing social values. However, challenges arise when the economic value of belis experiences inflation or a shift in meaning, potentially triggering financial burdens and conflict. Therefore, preserving the belis tradition requires adjustments to its values and implementation mechanisms to maintain its relevance, without losing the essence of respect and togetherness that are at the heart of Manggarai culture. This research makes an important contribution to the documentation and preservation of cultural heritage, and serves as a reference for local governments, traditional leaders, and the community in maintaining the sustainability of the paca or belis tradition.